2015
DOI: 10.1111/tmi.12540
|View full text |Cite
|
Sign up to set email alerts
|

Traditional vs. non‐traditional healing for minor and major morbidities in India: uses, cost and quality comparisons

Abstract: Abstractobjectives To examine the uses, cost and quality of care of traditional healing for short-term morbidities and major morbidities in India and to compare them with the non-traditional healing.methods We used data from a nationally representative survey, the India Human Development Survey (2004)(2005) and descriptive as well as bivariate analyses for the examination.results Use of traditional healing is much less common than use of non-traditional healing in both rural and urban areas and across all soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 18 publications
3
9
0
Order By: Relevance
“…However, our estimates are in line with a recent national survey showing that the use of traditional healers is low relative to the use of allopathic care for both minor and major morbidity, even in rural areas (51).…”
Section: Strengths and Limitationssupporting
confidence: 90%
See 1 more Smart Citation
“…However, our estimates are in line with a recent national survey showing that the use of traditional healers is low relative to the use of allopathic care for both minor and major morbidity, even in rural areas (51).…”
Section: Strengths and Limitationssupporting
confidence: 90%
“…showing that the use of traditional healers is low relative to the use of allopathic care for all health conditions, even in rural areas (51). This suggests that engaging with or influencing the use of traditional services should not be a major policy focus in improving care for depression in this context.…”
Section: Use Of Traditional Servicesmentioning
confidence: 99%
“…However, our estimates are in line with a recent national survey showing that the use of traditional healers is low relative to the use of allopathic care for both minor and major morbidity, even in rural areas (57).…”
Section: Strengths and Limitationssupporting
confidence: 90%
“…showing that the use of traditional healers is low relative to the use of allopathic care for all health conditions, even in rural areas (57). This suggests that engaging with or influencing the use of traditional services should not be a major policy focus in improving care for depression in this context.…”
Section: Use Of Traditional Servicesmentioning
confidence: 99%
“…We also found that only a showing that the use of traditional healers is low relative to the use of allopathic care for all health conditions, even in rural areas (51). This suggests that engaging with or influencing the use of traditional services should not be a major policy focus in improving care for depression in this context.…”
Section: Use Of Traditional Servicesmentioning
confidence: 76%